Pengaruh Strategi Coping Keluarga terhadap Keseimbangan antara Pekerjaan dan Keluarga serta Kesejahteraan Anggota Keluarga - Marfita Hikmatul Aini (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to investigate the relationship between family coping strategies and the balance between work and family, as well as the well-being of family members. This research uses a quantitative approach and survey methods to collect data from a sample of working family members. The research instrument includes questionnaires about family coping strategies, balance between work and family, and the psychological well-being of family members. Data analysis was carried out using appropriate statistical techniques.